EFEKTIVITAS PROBLEM BASED LEARNING DITINJAU DARI KEMAMPUAN BERPIKIR KRITIS DAN REPRESENTASI MATEMATIS - Sri Hastuti Noer; Pentatito Gunowibowo (Universitas Sultan Ageng Tirtayasa, 2018)
This study aims to determine the effectiveness of problem-based learning model in terms of the ability to think critically and mathematical representation of grade VIII students at a State Junior High School in Bandarlampung City. The population in this study are all students of class VIII distributed in eleven classes. The samples of this study are the students of two classes VIII whose class is selected by purposive random sampling technique. The research design is Pre-test Post-test Control Group Design. Mann-Whitney U non parametric test results on critical thinking and mathematical representation, indicating that H0 is rejected, thus drawn the conclusion that mathematical critical thinking and mathematical representation of students who follow PBL is higher than mathematical critical thinking and mathematical representation of students following learning conventional. The proportion test shows that the percentage of students who have critical thinking skills and mathematical representations are categorized well in the class using the PBL more than 60% of the number of students. The result of the research shows that learning with effective PBL model is viewed from critical thinking ability and student's mathematical representation Keywords: Problem Based Learning, Critical thinking, Mathematical Representation